Superconductivity in scandium borocarbide with orbital hybridization. (4th November 2020) - Wu, W; Li, Y J; Zhang, J H; Yu, Z H; Liu, Z Y; Zheng, P; Yang, H X; Dong, C; Liu, K; Xiang, T; Luo, J L
Abstract: Exploration of superconductivity in light element compounds has drawn considerable attention because those materials can easily realize the high T C superconductivity, such as LnNi2 B2 C ( T C  = 17 K), MgB2 ( T C  = 39 K), and very recently super-hydrides under pressure ( T C  = 250 K). Here we report the discovery of bulk superconductivity at 7.8 K in scandium borocarbide Sc20 BC27 with a tetragonal lattice which structure changes based on the compound of Sc3 C4 with very little B doping. Magnetization and specific heat measurements show bulk superconductivity. An upper critical field of H c2 (0) ∼ 8 T is determined. Low temperature specific-heat shows that this system is a BCS fully gapped s-wave superconductor. Electronic structure calculations demonstrate that compared with Sc3 C4 there are more orbital overlap and hybridization between Sc 3 d electrons and 2 p electrons of C-C(B)-C fragment in Sc20 BC27, which form a new electric conduction path of Sc-C(B)-Sc. Those changes influence the band structure at the Fermi level and may be the reason of superconductivity in Sc20 BC27 .